Performances of two commercially available Newcastle disease vaccines in Bangladesh: A case-control study (Bangladesh Journal of Microbiology, 2012)
The study was conducted to test the performances of two commercially available live vaccines named BCRDV1(VG/GA strain) and BCRDV2 (F-strain). A total of 90 day-old broiler birds were divided into three different  groups and the serum samples were collected at day 1, 7, 14, 21, 28 and 35; mean±SD of Haemgglutination  Inhibition (HI) titres (log2) were found as 8±0.00, 7.2±0.89, 6.1±0.9, 7.1±0.75, 5.7±0.72, 4.1±0.68 and 8±0.00, 6.0±0.76, 4.8±0.81, 5.8±0.83, 4.9±0.86, 3.8±0.77 in group I and group II respectively, which was significant (P< 0.01). In control (group III) the mean±SD was found to be 8±0.00, 5.8±0.87, 4.9±0.69, 4.1±0.48, 3.0±0.56 and